Experimental studies of two-stream mixing flows with vortex-generating tabs - Koh, Pak Keng. (2008)
A single inverted delta tab as well as an array of three tabs attached to the trailing edge of a splitter plate in a two-stream mixing layer had been studied experimentally using a three-component laser-Doppler anemometer. Detailed mean flow and turbulence measurements were obtained at a velocity ratio of 2:1 between the two co-flowing streams. The results showed that when the single tab was attached to the higher speed side, the streamwise vortices generated and the subsequent mixing were stronger and more intense than placing it on the low speed side. The effectiveness of both arrangements were quantified and compared in terms of mass flux entrainment with downstream distance. Their differences in the streamwise vorticity generation were explained in relation to the tab theory proposed by Bohl and Foss (1997). The decay of the streamwise vortices was rapid and took place within 10 tab heights from the trailing edge. The strength of streamwise vorticity appeared to have a direct correlation with the level of turbulence generated in the cross-stream directions. Attempts were also made to quantify the effect of each (streamwise vorticity) production term in the streamwise vorticity dynamics equation.